Weeds. Season three [videorecording (DVD)] - Kohan, Jenji, 1969- (Lionsgate, 2008)
Nancy Botwin is a soccer mom who had to learn how to deal - pot, that is - after the death of her husband. Now, her business is a hit and she finds she may be in over her head.